ZAKAT COMMUNITY DEVELOPMENT (ZCD) DALAM PEMBANGUNAN EKONOMI MASYARAKAT DESA TELUK PAYO KABUPATEN BANYUASIN - Shalihin, Rijalush (Nurani, 2016)
Poverty brings people to “kufr”, which resulted in a lot of people who do not want to implement a series of worship are obliged to do. Social life gradually ignored and no longer cared for in everyday people just thinks how do I get the money to make ends meet. In helping people who cannot afford, arranged in religion as well as helping the poor is by way of charity. “Zakat” should be done to help the poor to the prosperous and independent life. As it is now done program Zakat Community Development (ZCD) in Teluk Payo District of Banyuasin II Banyuasin in the development of poor communities in a comprehensive manner by integrating aspects of the economic and social aspects (education, health, religion, environment, and other social aspects) that Its main funding comes from “zakat, infaq”, and alms to realize a prosperous society and independent. ZCD program is a program to help poor people improve lives to become prosperous and independent manner to the poor given in accordance with the venture capital skills possessed.